Between Times: Phantasms of Homecoming in Postwar Germany (1945-1960) (KULT_online, 2011)
The anthology Heimkehr: Eine zentrale Kategorie der Nachkriegszeit. Geschichte, Literatur und Medien (Homecoming: A key category of the postwar period. History, Literature, and Media) discusses homecoming as an historical as well as aesthetic phenomenon in postwar Germany, and thus sheds new light on the complex relationship of continuities and ruptures after the 'zero hour'. What is more, since the articles present a very wide range of homecoming constellations and representations, the volume provides a useful introduction to German literary and cultural history of the postwar period.